Out and About With Tom and Pippo - Oxenbury, Helen (Walker Books Ltd, 1995)
Pippo the toy monkey is Tom's special friend and the two of them go everywhere together. They play in the garden and go to the shops and take their sleds out in the snow.
Keywords: Boys & Men; Juvenile Fiction